Effect of papaya seed supplementation on gas production activity in in vitro fermentation by rumen fluid - Rusli, Mohd Zharif (2016)
Papaya is commonly used as dessert and ingredient in the cooking. However, only the flesh has been consumed and the skin and seed will be discarded. The parts that did not consume will become waste and can attribute to pollution. Papaya seed is not being fully utilized by farmers. This study evaluates the comparative outcome of the Napier grass (Pennisetum purpureum) and papaya seed as supplement. These treatments are done for dry matter (DM), ash, crude protein (CP), neutral detergent fibre (NDF), acid detergent fibre (ADF), acid detergent lignin (ADL), in vitro gas production and in vitro dry matter digestibility (IVDMD) by using various parameters. 15 samples were collected randomly for this study including the control. Napier grass is used in this experiment acting as the basal diet for the ruminants. First sample is Treatment 1 = 100% Napier grass (n=3) followed by Treatment 2 = 99% Napier grass + 1% papaya seed (n=3), Treatment 3 = 98% Napier grass + 2% papaya seed (n=3) and Treatment 4 = 97% Napier grass + 3% papaya seed (n=3). Napier grass had been cut at week 6, dried in the oven at 105 °C until it reach the constant weight and the dried Napier grass was grinded into small pieces. Meanwhile papaya seed was collected at the stall nearby in Seri Serdang and dried it in the oven at 105 °C. Then, the papaya seed was grinded into small pieces. In the proximate analysis that had been done, the dry matter (DM), ash and neutral detergent fibre (NDF) had higher (P<0.05) than acid detergent fibre (ADF), acid detergent lignin (ADL), crude protein (CP) and crude fibre (CF). The DM, ash and NDF had significant difference between Treatment 1, Treatment 2, Treatment 3 and Treatment 4. From in vitro gas production analysis, it shows that the gas production had significance difference (p> 0.05) between the treatments. However, in vitro dry matter digestibility did not have significance difference between others treatments. For the recommendation, the researchers or farmers can exploit more about papaya seed because there are still more parameters that can be studied in the future.